2008
DOI: 10.1016/j.fishres.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental beam-trawling in Lanice conchilega reefs: Impact on the associated fauna

Abstract: To study fisheries impact at the species level in temperate sandy bottom areas, a controlled field manipulation experiment was designed focusing on areas with high densities of the habitat-structuring, tube-dwelling polychaete Lanice conchilega (i.e. L. conchilega reefs). The hypothesis was that the impact on L. conchilega would be minimal, but that the fauna benefiting from the biogenically structured habitat would be impacted by beam-trawling. In this study, the impact of beam-trawl passage on intertidal L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
(31 reference statements)
0
20
0
2
Order By: Relevance
“…Investigations by means of experimental trawling and empirical data showed that trawl fisheries increase the mortality of benthic species not caught in the nets but which are damaged by the passing gear (Bergman & van Santbrink, 2000;Mensink et al, 2000;Callaway et al, 2007;Rabaut et al, 2008). Moreover, fishing indirectly affects benthic communities by disturbing the sediment, altering seabed morphology, and increasing suspend solids in the water column (Watling, 2005), while individuals not killed may be left at the surface, increasing food availability for scavenging species (Frid et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations by means of experimental trawling and empirical data showed that trawl fisheries increase the mortality of benthic species not caught in the nets but which are damaged by the passing gear (Bergman & van Santbrink, 2000;Mensink et al, 2000;Callaway et al, 2007;Rabaut et al, 2008). Moreover, fishing indirectly affects benthic communities by disturbing the sediment, altering seabed morphology, and increasing suspend solids in the water column (Watling, 2005), while individuals not killed may be left at the surface, increasing food availability for scavenging species (Frid et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The large tidal flats result from the extreme megatidal regime (tidal range up to 15.5 m during spring tides) which dominates the BMSM (Larsonneur et al 1994). Boulogne is characterized by a tidal range up to 7 m and in comparison to the BMSM, the beach of Boulogne is less pristine and sheltered by two harbour walls (Rabaut et al 2008). The L. conchilega reef is situated in the lower intertidal and the majority is only exposed during extreme mean low water spring tide conditions.…”
Section: Study Areamentioning
confidence: 99%
“…The author indicates, however, that trawling in the medium to long-term can have consequences for the integrity of the reefs in the event of intensive fishing. For L. conchilega, the reef structure itself appears to be relatively resistant to fisheries impact (Rabaut, 2009) while the associated reef fauna experience an immediate impact (Rabaut et al, 2008). In the event of intensive beam-trawling, the reef structure will eventually disappear (Rabaut, 2009).…”
Section: Sublittoral Polychaete Worm Reefs On Sediment (Eunis A561)mentioning
confidence: 99%